MEDIA, DISINFORMATION, AND PUBLIC DECODING: AN ONLINE RECEPTION STUDY OF POLITICAL DISCOURSES - Sitorus, Rosalyn Magdalena br.; Nabila, Kanaya Nur; Fitriana, Fadila; Meisya, Shalsa Billa; Ginting, Valencia Laurence; Putri, S.S., M.Si., Dian Marisha (KLAUSA (Kajian Linguistik, Pembelajaran Bahasa, dan Sastra), 2025)
This study aims to analyze the political meaning influenced by the media and disinformation interpreted by Indonesian netizens in the online space, especially the connection with the influence of digital literacy, trust in institutions, and political discord. This study employs a qualitative reception analysis based on the Encoding/Decoding paradigm developed by Stuart Hall in 1980, which produced three reading positions: Dominant-hegemonic, Negotiated, and Oppositional. In addition, Critical discourse analysis (CDA) and digital ethnography also form the theoretical basis of this study. The data was collected from four main social media platforms in Indonesia, namely X (formerly Twitter), Instagram, TikTok, and Threads. The results show that Oppositional reading is the most common type of reading position (40%), followed by Dominant-hegemonic reading (35%) and Negotiated reading (25%). In general, the results show that Indonesian netizens display various decoding methods influenced by many backgrounds. Furthermore, it was also found that social media not only functions as a democratic space but also a space for the spread of disinformation. This study provides valuable insight into the political meanings influenced by the media and disinformation as interpreted by Indonesian netizens in the online space. Furthermore, this study contributes to understanding the relationship between political views and individual backgrounds.